LOW-POWER AND LOSSY NETWORKS OF WIRELESS SENSOR NETWORKS WITH PROTOCOLS ALGORITHM COMPARISON - Puput Dani Prasetyo Adi; Akio Kitagawa; Abdur Rabi; Nachrowie .; Rahman Arifuddin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
This research focuses on the energy efficiency needed by sensor nodes in the network architecture i.e, LEACH, HEED, LEACH-TLCH and PEGASIS according to the Routing Protocol Low Power and Lossy Network (RPL) pattern. In this research compared all algorithms based on the number of different sensor nodes. In this research, there is no focus on the type of sensor used but rests on the conclusions of the total results of the Overall energy (Avg_Energy) on clustering with the most appropriate networking strategy. In this research, 20, 50 and 100 nodes were tested in the HEED, LEACH, LEACH-TLCH and PEGASIS Algorithms respectively. furthermore, from the results of testing the total Power (mW) sensor obtained from the sum of 4 components of the Power Sensor node, i.e, CPU Power, Power LPM, Power TX (Transmitter) and Power Rx (Receiver), concludes the Power Consumption sensor node is affected by the number of nodes found on the Sensor Node Network Architecture, the lowest Power Consumption is the LEACH Algorithm Protocol with a total of 2,038 mW at 100 nodes, while the highest Power Consumption is LEACH-TLCH Protocol Algorithm 4,851 mW with 100 nodes followed by PEGASIS with total Consumption 4.31 mW. accordingly the simulation, At the lowest sensor node in this experiment, which is 20 nodes, LEACH produces the lowest total Power of 1.21 mW, while the highest is PEGASIS 1,361 mW. At the number of 50 nodes, the lowest is HEED with a power consumption of 1,558 mW, this result is only 0.046 mW with the LEACH Algorithm Protocol which is 1,604 mW. Furthermore, by building the right sensor network (WSN) it will support IoT networks with long sensor lifetime.